PENGARUH LATIHAN COGNITIVE SPECIFIC (GYAKU - TSUKI) TERHADAP KECEPATAN REAKSI PADA ATLET KUMITE DOJO DISNAKER KARATE CLUB - Lesmana, Bayu; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem of research is still low of reaction speed when performing gyaku – tsuki on the athlete of dojo disnaker karate club. Based on the problems, the writer gives the form of cognitive specific (gyaku – tsuki) exercise. This research is done to know how much effects cognitive specific (gyaku – tsuki) exercise to speed reaction to athelete kumite dojo disnaker karate club, when do the blow gyaku – tsuki get poin or not. The kind of research is experimental with design one group pretest-posttest design research. The population of research is athelete of dojo disnaker karate club which of 8 people. Altough example of technice is total sampling, and all of population become example. Instrument whole body reaction description analyzed and normality test is liliefors test on the significan level  (0,05) is rate pretest whole body reaction 0,1139. Next time, give exercise cognitive specific (gyaku – tsuki) about 14 time meeting on athelete amount 8 people. After that do post test whole body reaction produce avarage 0,2422. Based on data analisys pree test and post test there is a different number that increase by 0,014. From the test result analisys Thitung 2,475 and Ttabel 1,895 so Thitung > Ttabel. Can be conclude that cognitive specific exercise effect the result of increase reaction rate in athelete of kumite dojo disnaker karate club,Keywords : Cognitive Specific (Gyaku – Tsuki) , Speed Reaction